Erratum: Chitosan ameliorates Candida auris virulence in a Galleria mellonella infection model (American Society for Microbiology (2020) 64: 8 (e00476-20) DOI: 10.1128/AAC.00476-20) - Arias, Laís Salomão [UNESP]; Butcher, Mark C.; Short, Bryn; McKloud, Emily; Delaney, Chris; Kean, Ryan; Monteiro, Douglas Roberto [UNESP]; Williams, Craig; Ramage, Gordon; Brown, Jason L. (American Society for Microbiology, 2021)
This article was published on 22 July 2020 with a standard copyright line (“© 2020 American Society for Microbiology. All Rights Reserved.”). The authors elected to pay for open access for the article after publication, necessitating replacement of the original copyright line, and this change was made on 11 December 2020.